Experimental study of the Be-C phase diagram. (March 2019) - Liu, Kun; Huang, Xiaozhong; Fu, Zeyu; Wang, Peisheng; Du, Yong; Yang, Haitang
Abstract: The phase equilibria in the Be-C system were studied via experiment technique. Eleven key alloys were prepared by powder metallurgy method. X-ray diffraction (XRD), scanning electron microscopy (SEM) and differential thermal analysis (DTA) were used to determine phase compositions and phase transition temperatures. For the first time, the entire phase diagram for the Be-C system was obtained in the present work. The present work confirms that there is only one intermediate compound Be2 C in this system. One allotropic transformation ((βBe) ↔ (αBe)) and two eutectic reactions (L ↔ (βBe) + Be2 C and L ↔ Be2 C + (C)) were determined.